Design of reconfigurable active integrated microstrip antenna with switchable low‐noise amplifier/power amplifier performances for wireless local area network and WiMAX applications. Issue 9 (1st June 2015) - Valizade, Arash; Rezaei, Pejman; Orouji, Ali Asghar
Abstract : A novel design of reconfigurable monopole microstrip active integrated antenna (AIA) for wireless local area network (WLAN) and Worldwide Interoperability for Microwave Access (WiMAX) applications is presented and discussed in this study. The primary designed reconfigurable passive antenna is capable of supporting switchable single/dual band performances while having a compact dimension of 12 × 18 mm 2 . The proposed reconfigurable passive antenna is integrated with an interdigital filter and a reconfigurable switchable power/low‐noise amplifier (LNA) (power amplifier – PA, LNA) forming a single‐port microstrip AIA which can be used as a full‐duplex switchable transceiver in which the need for additional filters is eliminated because of its reconfigurable structure. A 2.3–2.56 GHz (WLAN) with 12.3 dB (PA) gain improvement and 3.3–3.59 GHz (WiMAX) with 8.5 dB (LNA) gain improvement are supported at switchable performances of the fabricated reconfigurable AIA. Measured results show that the designed passive and active antennas have proper almost omnidirectional radiation characteristics at their desired operation frequencies which is suitable for WLAN and WiMAX applications.